Low-Abundance Members of the Firmicutes Facilitate Bioremediation of Soil Impacted by Highly Acidic Mine Drainage From the Malanjkhand Copper Project, India - Gupta, Abhishek; Dutta, Avishek; Sarkar, Jayeeta; Panigrahi, Mruganka Kumar; Sar, Pinaki (Frontiers in Microbiology, 2018)
Sulfate- and iron- reducing heterotrophic bacteria represented minor proportion of the indigenous microbial community of highly acidic, oligotrophic acid mine drainage (AMD), but they can be successfully stimulated for in-situ bioremediation of a an AMD impacted soil (AIS). These anaerobic microorganisms although played central role in sulfate- and metal- removal, they remained inactive in the AIS due to the paucity of organic carbon and extreme acidity of the local environment. The present study investigated the scope for increasing the abundance and activity of inhabitant sulfate- and iron- reducing bacterial populations of an AIS from Malanjkhand copper project. An AIS of pH 3.5, high soluble SO42- (7838 mg/l) and Fe (179 mg/l) content was amended with nutrients (cysteine and lactate). Thorough geochemical analysis, 16S rRNA gene amplicon sequencing and qPCR highlighted the intrinsic metabolic abilities of native bacteria in AMD bioremediation. Following 180 days incubation, the nutrient amended AIS showed marked increase in pH (to 6.6) and reduction in soluble -SO42- (95 %), -Fe (50 %) and other heavy metals. Concomitant to physicochemical changes a vivid shift in microbial community composition was observed. Members of the Firmicutes present as a minor group (1.5 % of total community) in AIS was emerged as the single most abundant taxon (~56 %) following nutrient amendments. Organisms affiliated to Clostridiaceae, Peptococcaceae, Veillonellaceae, Christensenellaceae, Lachnospiraceae, Bacillaceae, etc. known for their fermentative, iron and sulfate reducing abilities were prevailed in the amended samples. qPCR data corroborated with this change and further revealed an increase in abundance of dissimilatory sulfite reductase gene (dsrB) and specific bacterial taxa. Involvement of these enhanced populations in reductive processes was validated by further enrichments and growth in sulfate- and iron- reducing media. Amplicon sequencing of these enrichments confirmed growth of Firmicutes members and proved their sulfate- and iron- reduction abilities. This study provided a better insight on ecological perspective of Firmicutes members within the AMD impacted sites, particularly their involvement in sulfate- and iron- reduction processes, in situ pH management and bioremediation.